2015
DOI: 10.1002/humu.22740
|View full text |Cite
|
Sign up to set email alerts
|

Somatic MMR Gene Mutations as a Cause for MSI-H Sebaceous Neoplasms in Muir-Torre Syndrome-Like Patients

Abstract: Sebaceous neoplasms are a major clinical feature of Muir-Torre syndrome (MTS) associated with visceral malignancies, especially colorectal and endometrial tumors. The diagnosis of MTS relies largely on the microsatellite instability (MSI) phenotype in tumors, suggesting germline mutations in DNA mismatch repair (MMR) genes responsible for the inherited disease. We hypothesized that in some MSI-H sebaceous tumors, acquired rather than inherited mutations in MMR genes could be involved. Using next-generation seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
(12 reference statements)
4
18
0
Order By: Relevance
“…Indel-rich MSI SeC appear to be initiated by inactivating mutations in mismatch-repair genes (which can be either germline or somatic), while SeC with UV-damage-associated mutational signatures develop on heavily sun-damaged skin. Although sebaceous neoplasms have been reported anecdotally to harbor somatic mutations in mismatch-repair genes 8 , 22 , our results show that virtually all MSI class SeC arise from either a germline or somatic mutation in this pathway. A third, previously undescribed pauci-mutational class is primarily represented by facial SeC.…”
Section: Discussionmentioning
confidence: 49%
“…Indel-rich MSI SeC appear to be initiated by inactivating mutations in mismatch-repair genes (which can be either germline or somatic), while SeC with UV-damage-associated mutational signatures develop on heavily sun-damaged skin. Although sebaceous neoplasms have been reported anecdotally to harbor somatic mutations in mismatch-repair genes 8 , 22 , our results show that virtually all MSI class SeC arise from either a germline or somatic mutation in this pathway. A third, previously undescribed pauci-mutational class is primarily represented by facial SeC.…”
Section: Discussionmentioning
confidence: 49%
“…Smaller studies have suggested that universal tumor testing with MMR IHC also may be effective in screening for Lynch syndrome among individuals with less common forms of Lynch syndrome‐associated cancer, such as upper tract urothelial cancer (ie, renal pelvis and ureter) . Caution should be used when interpreting MMR IHC results from sebaceous neoplasms of the skin, which, compared with other Lynch‐associated neoplasms, appear disproportionately likely to demonstrate sporadic MSI‐H/MMR deficiency in the absence of underlying Lynch syndrome . It is also important to note that, for rectal cancers, when radiotherapy is administered before surgery, the MMR IHC assay can be inaccurate, primarily because of artifactual loss of MSH6 in the surgical specimen .…”
Section: Current Status Of Germline and Somatic Dna Testingmentioning
confidence: 99%
“…69 Caution should be used when interpreting MMR IHC results from sebaceous neoplasms of the skin, which, compared with other Lynch-associated neoplasms, appear disproportionately likely to demonstrate sporadic MSI-H/MMR deficiency in the absence of underlying Lynch syndrome. [70][71][72] It is also important to note that, for rectal cancers, when radiotherapy is administered before surgery, the MMR IHC assay can be inaccurate, primarily because of artifactual loss of MSH6 in the surgical specimen. 73 Thus, pretherapy tissue or polymerase chain reaction-based MSI testing should be the preferred approach in this situation.…”
Section: Variants) Including Some Rare Individuals With Pathogenic Gmentioning
confidence: 99%
“…The remaining MSI-H tumors were, until recently, believed to be the indication of the presence of a germline mutation in the context of Lynch or Lynch-related syndromes. However, recent studies have shown that a small subset of those MSI-H tumors can be the consequence of a pure somatic MMR inactivation through two somatic hits 16 , 17 . Still, because the majority of the MSI-H tumors are germline-related, the testing for the MSI-H phenotype combined with immunostaining for a loss-of-expression of one of four MMR proteins (MLH1, MSH2, MSH6 and PMS2) is considered to be an efficient way to screen for Lynch or related syndromes.…”
Section: Genetics and Clinical Impact Of Predisposition To Lynch Syndmentioning
confidence: 99%